2010
DOI: 10.1124/dmd.110.035857
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Oral Pharmacokinetics of cMet Kinase Inhibitors in Humans: Physiologically Based Pharmacokinetic Model Versus Traditional One-Compartment Model

Abstract: ABSTRACT:The objective of this study was to assess the physiologically based error) and PF04217903 (1.3-fold error) compared with the onecompartment PK model (1.8-and 1.9-fold errors, respectively). Of more importance, the simulated plasma concentration-time profiles of PF02341066 and PF04217903 by PBPK modeling seemed to be consistent with the observed profiles showing multiexponential declines, resulting in more accurate prediction of the apparent half-lives (t 1/2 ): the observed and predicted t 1/2 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…Yamazaki et al (2011) demonstrated that a PBPK model provided better prediction of the maximum plasma concentration and the area under the plasma concentration-time curves for two compounds than a traditional one-compartment model based on CL and V ss predicted by allometric scaling. Comparative analysis between the Dedrick and PBPK approaches was conducted by Jones et al (2006), who employed 19 compounds with a wide range of CL and V ss .…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki et al (2011) demonstrated that a PBPK model provided better prediction of the maximum plasma concentration and the area under the plasma concentration-time curves for two compounds than a traditional one-compartment model based on CL and V ss predicted by allometric scaling. Comparative analysis between the Dedrick and PBPK approaches was conducted by Jones et al (2006), who employed 19 compounds with a wide range of CL and V ss .…”
Section: Discussionmentioning
confidence: 99%
“…In GTL16 GC xenograft models, crizotinib-mediated MET inhibition was achieved with an in vivo EC 50 of 1.5 nM free, that was approximately 7-fold lower than in vitro value (10 nM) (46). While there are several potential reasons for such a disconnect between in vitro and in vivo EC 50 estimates, a correction for non-specific binding of crizotinib in the in vitro cell-based assay might be the one to be considered since crizotinib showed relatively high non-specific binding (∼90%) in hepatic microsomes and hepatocytes, along with high plasma protein binding of 91 to 96% across species (47). Another potential contributing factor could be the impact of subcutaneous inoculation of tumor cells on the expression levels of drug-metabolizing enzymes and transporters in mouse xenograft models (48), since crizotinib has been characterized as a substrate of CYP3A isozymes and multidrug-resistance transport protein, P-glycoprotein (44).…”
Section: Building Pkpd Understanding In Nonclinical Modelsmentioning
confidence: 99%
“…Crizotinib consistently showed a relatively large V ss (13 to 25 L/kg) across species including humans after an intravenous administration, and crizotinib C max was occurred at relatively later time point (e.g., 4 to 6 h) after an oral administration across species (44,47). Crizotinib has an extensive tumor distribution profiles with an approximate tumor/plasma AUC ratio of 4 at steady-state (in-house data).…”
Section: Building Pkpd Understanding In Nonclinical Modelsmentioning
confidence: 99%
“…Reports of a phase II trial with AMG 102 identified that although the drug brought about tumour burden reduction and long-term disease stability, it was unclear from the study whether this drug is capable of tumour growth inhibition in a histologically diverse population of patients with mRCC (Schoffski et al, 2010). Other drugs currently in development include foretinib (GSK1363089) an oral multi kinase inhibitor of MET and VEGFRs (Kataoka et al, 2011) (Yamazaki et al, 2011). The efficacy of these drugs have yet to be investigated in patients with RCC.…”
Section: Hgf/met Signallingmentioning
confidence: 99%